Käfka's Influence on Camara Laye's Le regard du roi - Patricia A. Deduck (Studies in 20th & 21st Century Literature, 1980)
In Le regard du roi, Camara Laye attempted to assimilate into his own fictional world the structure, techniques, and themes which he found in the works of Kafka. A close analysis of the novel reveals not only significant influence, but direct imitation of Kafka. Although certain Kafkaesque techniques—for example, the limited perspective, and the dispensation with time and space as measurable quantities—are often used effectively in the novel, they lose much of their intricate complexity in a fictional world allowing, as Laye's does, for positive resolution. Such techniques become integral and meaningful elements only when Laye uses them within the context of his négritude theme.
Keywords: Käfka; Camara Laye; Le regard du roi; fiction; Kafka techniques; kafka themes; kafkaesque technique; limited perspective; time; space; négritude theme